2021
DOI: 10.14336/ad.2020.0709
|View full text |Cite
|
Sign up to set email alerts
|

NIHSS Consciousness Score Combined with ASPECTS is a Favorable Predictor of Functional Outcome post Endovascular Recanalization in Stroke Patients

Abstract: Although revascularization rates after endovascular thrombectomy for large vessel acute ischemic stroke (AIS) are high (71%), only 46% of patients achieve functional independence at 90 days. The present study was designed to explore a new method for predicting the functional prognosis of AIS patients after endovascular recanalization. A total of 200 anterior circulation stroke patients who received endovascular therapy were enrolled. Logistic regression analysis of clinical characteristics on functional indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
5
24
0
Order By: Relevance
“…Our meta-analysis revealed a clear association of decreasing ASPECTS with odds of poor functional outcomes regardless of the RT received. This is in line with the previous studies that found that decreased ASPECTS are associated with worse functional outcomes [ 16 , 19 , 22 , 33 , 35 , 38 ]. Despite the study design and cohort size, most of the included studies in this meta-analysis found a significant relationship between poor functional outcomes and ASPECTS cut-off points of 6 [ 27 , 30 , 36 , 37 , 38 ], 7 [ 24 , 25 , 26 , 34 , 38 ] and 8 [ 6 , 23 , 29 , 31 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our meta-analysis revealed a clear association of decreasing ASPECTS with odds of poor functional outcomes regardless of the RT received. This is in line with the previous studies that found that decreased ASPECTS are associated with worse functional outcomes [ 16 , 19 , 22 , 33 , 35 , 38 ]. Despite the study design and cohort size, most of the included studies in this meta-analysis found a significant relationship between poor functional outcomes and ASPECTS cut-off points of 6 [ 27 , 30 , 36 , 37 , 38 ], 7 [ 24 , 25 , 26 , 34 , 38 ] and 8 [ 6 , 23 , 29 , 31 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…The 6 studies, comprising 735 patients, included in the meta-analysis demonstrated that there was a significant association of increasing ASPECTS with poor functional outcomes at 90 days (SMD = −1.15; 95% CI −1.77–−0.52; p < 0.0001) ( Figure 3 ) [ 16 , 19 , 22 , 33 , 35 , 38 ]. Moderate to considerable heterogeneity was found between the studies (I 2 = 93.1%, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…The association is easy to understand because NIHSS is the most commonly used scale to evaluate the neurologic de cit in stroke patients. Numerous studies have also con rmed the predictive effect of NIHSS on prognosis of PCIS and basilar artery occlusion patients [26][27][28][29] . In the present study, besides the NIHSS score, we also examined the predictive value of pc-ASPECTS, which has been widely studied in PCIS patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Unfortunately, effective treatment strategies for ischemic stroke are limited, and include intravenous thrombolysis and mechanical thrombectomy that aim to restore the blood supply to the affected brain region. 4 However, there is a potential risk of recanalization, that is, reperfusion injury, manifested by increased cerebral edema, infarct progression, hemorrhagic stroke, and neurological deterioration. 5 Previous studies have suggested that these changes may be associated with excitotoxicity, neuroinflammation, oxidative stress, calcium overload, autophagy, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Many patients were discharged with varying degrees of sequelae that seriously affect the quality of life 3 . Unfortunately, effective treatment strategies for ischemic stroke are limited, and include intravenous thrombolysis and mechanical thrombectomy that aim to restore the blood supply to the affected brain region 4 . However, there is a potential risk of recanalization, that is, reperfusion injury, manifested by increased cerebral edema, infarct progression, hemorrhagic stroke, and neurological deterioration 5 .…”
Section: Introductionmentioning
confidence: 99%